Fieldwork in tourism : methods, issues and reflections - Hall, Colin Michael, 1961- (Routledge studies in contemporary geographies of leisure, tourism, and mobility., 2011)
This book incorporates a rich and diverse set of fieldwork experiences, insights and reflections on conducting fieldwork in different settings, the problems that emerge, the solutions that were developed, and the realities of being 'in the field'. Fieldwork in Tourism is an essential guide for Tourism higher level students, academics and researchers embarking on research in this field."--pub. desc.